2007
DOI: 10.1177/230949900701500308
|View full text |Cite
|
Sign up to set email alerts
|

Salter Innominate Osteotomy for Treatment of Developmental Dysplasia of the Hip

Abstract: Open reduction and SIO without preoperative traction is effective for the management of DDH in children younger than 6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
4
10
0
2
Order By: Relevance
“…Our findings show a shorter range of interval in evaluated patients after surgical reduction in comparison with other studies [25] using Salter’s technique, while mean angle values were in line with other authors’ results [25]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings show a shorter range of interval in evaluated patients after surgical reduction in comparison with other studies [25] using Salter’s technique, while mean angle values were in line with other authors’ results [25]. …”
Section: Discussionsupporting
confidence: 92%
“…Since angle values less than 15 degrees [26] are considered for surgical reduction, performed Salter’s innominate osteotomy gains post-surgical trends of angles regarding Wiberg’s centre-edge angle above 25 degrees [27] in all age groups, suggesting its beneficial role in correction of DDH. Our approaches with Salter’s technique give post-surgical mean angle values that are in line with other studies, especially in patients from the first two age groups [25]. …”
Section: Discussionsupporting
confidence: 88%
“…The remodelling potential of the acetabulum has been shown to diminish around the age of 5 years, with Brougham et al [ 22 ] finding a range of 17 months to 8 years for the cessation of development. The evidence in the literature is not conclusive regarding the optimum age for surgery for the correction of residual dysplasia [ 9 , 23 , 24 ], and no published consensus exists. This uncertainty as to best practice is borne out in our results, with no intra- or inter-regional pattern evident for preferred age for osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that these patient factors are included in the decision-making matrix of 59 % of surgeons who responded. The eponymous osteotomies described in the literature used in this age group are the Dega osteotomy [ 10 ] and the Pemberton osteotomy [ 25 ], both of which hinge at the triradiate cartilage, and the Salter osteotomy [ 11 , 24 ], which hinges at the pubic symphysis. Our survey has shown that 35 % of surgeons choose their osteotomy regardless of acetabular morphology or imaging.…”
Section: Discussionmentioning
confidence: 99%
“…For children under 3 months, the preferred treatment is Pavlik bandaging and/or dynamic hip orthosis; for children of 3–18 months (with/without arthrography), closed and open reductions (ORs) are most common; and for children 18 months and older, pelvic osteotomies are used. 1 2 3 4 5 6 7 8 9 Pemberton described an acetabuloplasty, now called the Pemberton pericapsular osteotomy (PPO), where an iliac osteotomy ended at the posterior limb of the triradiate cartilage and the anterolateral rim of the acetabulum was hinged downward and laterally. 3 PPO performed with OR may be adequate for DDH patients over 18 months, but femoral shortening (FS) osteotomy is often performed alongside pelvic osteotomy for patients aged 3 years plus.…”
Section: Introductionmentioning
confidence: 99%